TRANSFORMASI AI PADA ERA DIGITAL: TANTANGAN DAN PELUANG BAGI GEN-Z - Budi Wasito; Sigit Birowo; Liaw Bunfa; Brastoro, Brastoro (JURNAL PENGABDIAN MANDIRI, 2025)
Sharing Session activities in the framework of the International Student Creativity Program (PKM) with the theme “AI Transformation in the Digital Age: Challenges and Opportunities for Gen-Z”. This activity is part of the National Leader Forum (NLF) which was held in Palembang on September 13-15, 2024. The main purpose of this activity is to provide an in-depth understanding of the rapid development of artificial intelligence (AI) technology and its impact on the lives of the younger generation, especially Gen-Z. In this digital era, AI transformation not only presents various challenges but also opens up great opportunities for creativity and innovation in various fields. The implementation of this activity can provide tangible benefits for the development of the abilities and insights of the younger generation in facing challenges and utilizing opportunities in the era of fast-paced digital transformation as well as in the future. can continue to be a sustainable agenda to support the development of student competencies and insights in facing a dynamic digital era.